THE IMPLEMENTATION OF MARINE TOURISM MANAGEMENT POLICY IN THE BANGGAI ISLANDS DISTRICT - Frederikus Antonius Mana; Werenfridus Talia; Muhammad Novan Prasetya; Syahrabuddin Husen Enala; Umiyati Haris (Nusantara Hasana Journal, 2023)
The tourism management policy of Banggai Islands Regency is contained in the Regency's RPJMD. Tourism programs in the RPJMD of Banggai Islands Regency in 2011-2016, namely: (1) tourism basic information provision program, (2) tourism management program, (3) tourism promotion management program, (4) tourism promotion partnership management program, (5) tourism partnership and interconnectivity management program, and (6) tourism event implementation program. Various tourism potentials in Banggai Islands have not been developed optimally. This shows that there are problems in the implementation of tourism management policies in the Banggai Islands Regency. This research used a qualitative research method with a locus in Banggai Islands Regency, Central Sulawesi. The types of data in this research are primary data and secondary data. Data collection used observation and interview techniques. The results showed that the performance of marine tourism management policy implementation in Banggai Islands Regency as seen from the indicators of responsiveness, program alignment with needs and efficiency.